2017
DOI: 10.1515/msp-2017-0050
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the power losses in the ferromagnetic materials

Abstract: In this paper, the problem of describing power losses in ferromagnetic materials is considered. The limitations of Steinmetz formula are shown and a new analytical description of losses in a considered material is proposed. The correctness of the developed description is demonstrated experimentally by comparing the results of calculation with the catalogue characteristics for different ferromagnetic materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…The results given in Reference [20] showed that differences between values of power dissipated in the inductor core computed with the use of the models described in References [13,23] and the catalog data reached as high as 60%. In contrast, the results of computations performed with the use of the core model described in Reference [3] adequately fit the catalog data. In practice, this means that the use of classical models to describe power losses in the core, given in References [13,23] makes it impossible to obtain correctly computed values of power losses.…”
Section: Model Of Power Losses In the Core Of An Inductormentioning
confidence: 85%
See 4 more Smart Citations
“…The results given in Reference [20] showed that differences between values of power dissipated in the inductor core computed with the use of the models described in References [13,23] and the catalog data reached as high as 60%. In contrast, the results of computations performed with the use of the core model described in Reference [3] adequately fit the catalog data. In practice, this means that the use of classical models to describe power losses in the core, given in References [13,23] makes it impossible to obtain correctly computed values of power losses.…”
Section: Model Of Power Losses In the Core Of An Inductormentioning
confidence: 85%
“…In practice, this means that the use of classical models to describe power losses in the core, given in References [13,23] makes it impossible to obtain correctly computed values of power losses. Differences between the values obtained with the authors' model given in Reference [3] and the considered literature models are largest at high values of temperature, frequency of the control signal, and input voltage [20]. In turn, the results given in Reference [12] showed that, in order to compute power losses of the inductor core included in the boost converter, it is essential to take into account the shape of the waveform of magnetic flux density and the influence of temperature and frequency on the properties of magnetic materials.…”
Section: Model Of Power Losses In the Core Of An Inductormentioning
confidence: 97%
See 3 more Smart Citations